Effect of Plant Growth Promoting Rhizobacteria (PGPR) on the Growth and Yield of Rice Plants (Oryza sativa L.) - Firdha Nova Romadhona; Nefy Dina Mariati; Bayu Laksamana; Dukat Dukat (Jurnal Agrosci, 2025)
Abstract Background. The main agricultural product that yields rice as a primary food source in Indonesia is rice plants (Oryza sativa L. ). This crop is vital for fulfilling the country's food demands. A significant challenge to achieving food security and independence nationally is the reduction in productivity, which results from soil fertility loss due to the overuse of chemical fertilizers. Aims. To address these challenges, strategies have been put in place, such as incorporating organic materials and utilizing soil microbes, which can be included in contemporary agricultural practices. The use of Plant Growth Promoting Rhizobacteria (PGPR) is one method to enhance plant growth. This study aimed to investigate the influence of PGPR on the growth and yield of rice plants (Oryza sativa L). Methods. The study was conducted from April to August 2025 in Babadan Village, located within Cirebon Regency in West Java. The experimental design utilized a Group Random Design (RAK) featuring six different PGPR concentrations, tested four times, resulting in 24 experimental plot units: P0 (control), P1 (5 ml/l), P2 (10 ml/l), P3 (15 ml/l), P4 (20 ml/l), and P5 (25 ml/l). Observations included various metrics such as plant height, number of sprouts in each clump, leaf area, root volume, plant growth rate (LPT), number of productive sprouts per clump, length of panicles, total grains per panicle, the percentage of filled grains per clump, weight of filled grains per clump, weight of 1,000 grains, total weight of harvested dry grains per clump, total weight of harvested dry grains per plot, and weight of milled dry grains per plot. Result. The findings indicated that PGPR positively affected multiple growth and yield characteristics. Specifically, PGPR application significantly influenced plant height, root volume, the number of panicles per clump, length of panicles per clump, grains per panicle, the percentage of grains per clump, weight of grains per clump, weight of 1,000 grains, weight of harvested dry grains (GKP) per clump, weight of GKP per plot, and weight of milled dry grains (GKG) per plot. Conclusion. The highest yields of harvested dry grains (GKP) and milled dry grains (GKG) per plot occurred with the PGPR treatment at a concentration of 15 ml/l, resulting in 6. 13 kg and 5. 81 kg, respectively. Implementation. Farmers in Babadan Village can adopt the PGPR treatment at a concentration of 15 ml/l.